Behavioral Study of Diabetes Mellitus Patients in Blood Glucose Control: A Phenomenological Study - Febriyanti, Febriyanti; Masrul, Masrul; Najirman, Najirman; Indrapriyatna, Ahmad Syafruddin; Yunir, Em; Mudjiran, Mudjiran; Semiarty, Rima; Yulia, Dwi (GLOBAL HEALTH SCIENCE GROUP, 2024)
The disease pattern in Indonesia is currently shifting from infectious diseases to degenerative diseases. This pattern is accompanied by the problem of a double burden of disease. The incidence of degenerative diseases is increasing along with changes in lifestyle and environmental behavior. One of the threats of degenerative diseases to public health is diabetes mellitus. The prevalence of diabetes in people aged over 15 years increased from 10.9% in 2018 to 11.7% in 2023. This shows that this disease is not only a problem for the elderly but also affects the productive age group. The main causes include unhealthy diet, lack of physical activity, and obesity. This study aims to observe and explore the behavior of people with diabetes in controlling blood glucose while suffering from diabetes. The research method used in this study is qualitative research with a phenomenological approach, with the informant selection technique using the snowball technique of 25 people. The main instrument of qualitative research is the researcher herself. The researcher is a nurse with a Masters in Nursing. The researcher as a facilitator also uses the tools used in the study as data collection instruments, namely the Digital Voice Recorder in this case the researcher's cellphone (Oppo A92) and interview guidelines and field notes and the researcher conducted in-depth interviews for approximately 3 weeks, data processing and data analysis using the Colaizzi method which consists of seven stages. Based on the results of in-depth interviews with 25 informants, 16 themes of the phenomenon of factors causing uncontrolled blood glucose were obtained, including incorrect knowledge about diabetes, the assumption that diabetes is a harmless disease, boredom factors in managing diet, poor behavior in daily eating habits, taking medication not according to the given dose, rarely or not doing sports activities, having an attitude that ignores the rules in following a diet while suffering from diabetes, information obtained from health workers and family is minimal, information from various media such as the internet is not utilized, limited health workers in providing education, feelings of hopelessness while suffering from diabetes mellitus, feeling that they do not get support from family or health workers in treating diabetes while suffering from diabetes mellitus, alternatives to drugs from the hospital are taking herbal medicines. The phenomenon of the dominant factors causing uncontrolled blood glucose is incorrect knowledge about diabetes, as well as the assumption that diabetes is a harmless disease, as well as boredom factors in regulating diet, and poor behavior in daily eating habits, as well as rarely or never doing sports activities, and having attitudes and behaviors that ignore the rules in undergoing treatment while suffering from diabetes.